Case report: Functional characterization of a de novo c.145G>A p.Val49Met pathogenic variant in a case of PIGA-CDG with megacolon - Salinas-Marín, Roberta; Murakami, Yoshiko; González-Domínguez, Carlos Alberto; Cruz-Muñoz, Mario Ernesto; Mora-Montes, Héctor Manuel; Morava, Eva; Kinoshita, Taroh; Monroy-Santoyo, Susana; Martínez-Duncker, Iván (Frontiers in Genetics, 2022)
A subgroup of Congenital Disorders of Glycosylation (CDG) include inherited GPI-anchor deficiencies (IGD) that affect the biosynthesis of glycophosphatidylinositol (GPI) anchors, including the first reaction catalyzed by the X-linked PIGA. Here we show the first PIGA-CDG case reported in Mexico in a male child with a moderate to severe phenotype characterized by neurological and gastrointestinal symptoms, including megacolon. Exome sequencing identified the hemizygous variant PIGA c.145G>A (p.Val49Met), confirmed by Sanger sequencing and characterized as de novo. The pathogenicity of this variant was characterized by flow cytometry and complementation assays in PIGA knockout (KO) cells.